The importance of grain legumes in cropping systems in Africa - Nangju, D. (1975)
Grain legumes play an important role in cropping systems in Africa by virtue of their short duration, drought tolerance, ability to fix nitrogen from atmospheric air, and ability to grow in depleted soils and in association with cereals and root crops. In addition, grain legumes are important sources of vegetable proteins, vitamin B and calcium particularly for vegetarian diets during the hungry season. Different species of grain legumeg are grown in various forms of cropping systems. Their performance under mixed cropp ins system and their contribution to soil fertility are reviewed. It is concluded that under the present management practices in Africa, grain legumes probably contribute very little toward maintaining or enhancing soil fertility, and that higher yields obtained under mixed cropping may be attributed mainly to greater utilization of environmental resources, and lower incidence of diseases and insects. Research is urgently required to improve the contribution of grain legumes to nitrogen requirements of companion crops or the following crops in view of the high cost of nitrogen fertilizers.